2020
DOI: 10.1021/acsearthspacechem.0c00209
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Sulfur Species Formed upon Heterogeneous OH Oxidation of Organosulfates: A Case Study of Methyl Sulfate

Abstract: Recent studies reveal that organosulfates at the particle surface can be oxidized by gas-phase OH radicals with significant rates. Inorganic sulfur species, such as the bisulfate ion (HSO 4 − ) and sulfate ion (SO 4 2− ), can be formed upon these heterogeneous oxidation processes through the formation and subsequent reactions of sulfate radical anion (SO 4 •− ) in the particle phase. However, the amount of inorganic sulfur species produced in these heterogeneous oxidation reactions is not known. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 55 publications
2
24
1
Order By: Relevance
“…Hydroxyl radicals (·OH) are important oxidants in the atmospheric environment. In the aqueous phase, OH radicals can be formed from various sources including uptake from the gas phase, the Fenton reaction of H 2 O 2 with Fe 2+ , photolysis of H 2 O 2 , etc. , In the aqueous phases of aerosols and cloud droplets, the OH radicals can react with glutaric acid (HOOC­(CH 2 ) 3 COOH) and adipic acid (HOOC­(CH 2 ) 4 COOH) by H atom abstraction . The alkyl radicals formed can then generate higher level oxidation products in the presence of oxygen. , In addition, an electron transfer reaction also can occur between the deprotonated carboxyl group and ·OH. , Based on the speciation calculation, glutaric acid and adipic acid are fully protonated (H 2 A) when the pH value is lower than 2 and are fully deprotonated (A 2– ) when the pH value is higher than 8. , In previous studies, the OH radical reaction rate constants of the two DCAs in the H 2 A and A 2– forms have been determined at room temperature at pH values of 2 and 9 by Scholes and Willson and Herrmann .…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyl radicals (·OH) are important oxidants in the atmospheric environment. In the aqueous phase, OH radicals can be formed from various sources including uptake from the gas phase, the Fenton reaction of H 2 O 2 with Fe 2+ , photolysis of H 2 O 2 , etc. , In the aqueous phases of aerosols and cloud droplets, the OH radicals can react with glutaric acid (HOOC­(CH 2 ) 3 COOH) and adipic acid (HOOC­(CH 2 ) 4 COOH) by H atom abstraction . The alkyl radicals formed can then generate higher level oxidation products in the presence of oxygen. , In addition, an electron transfer reaction also can occur between the deprotonated carboxyl group and ·OH. , Based on the speciation calculation, glutaric acid and adipic acid are fully protonated (H 2 A) when the pH value is lower than 2 and are fully deprotonated (A 2– ) when the pH value is higher than 8. , In previous studies, the OH radical reaction rate constants of the two DCAs in the H 2 A and A 2– forms have been determined at room temperature at pH values of 2 and 9 by Scholes and Willson and Herrmann .…”
Section: Introductionmentioning
confidence: 99%
“…(Yu et al, 2018) The synergy of NO2 and O2, which involved mechanisms such as chain reactions, resulted in much faster sulfate formation than the sum of the reaction rates with NO2 and with O2 alone. These reports show the usefulness of single-particle Raman spectroscopy in studying the multiphase formation of particulate (Xu et al, 2020b) and organo-sulfate functional groups are also Raman-active. (Bondy et al, 2018) Raman spectroscopy may find applications in the study of organo-sulfates.…”
Section: Multiphase Formation Of Secondary Inorganic Aerosols (Sia)mentioning
confidence: 83%
“…Importantly, several unidentified OS can be explained, in respect of formation mechanisms, by heterogeneous OH oxidation of OS. 54,57 Regarding the formation of other products, Xu et al 56 reported the significant molar yield of inorganic sulfates from methyl OS, defined as the numbers of moles of bisulfate (HSO 4 -) and sulfate (SO 4 -) ions generated per mole of parent OS reacted, to be mounted up to (62 ± 18) % upon heterogeneous OH oxidation. From these findings, it is reasonable to hypothesize that a portion of OS may not be as atmospherically stable species as previously presumed.…”
Section: Introductionmentioning
confidence: 99%